Philippine criminal law dictionary - Salinas, Karis Dawn M. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
Not everyone possesses legal knowledge. Unfortunately, the poor and the uneducated are the ones more involved in crimes. Since English is the chosen language of the practice of law in the Philippines, this creates alienation among those accused of crimes from the legal knowledge. The main problem is that it is too difficult to quickly find the required legal information.